PERAN IBU DALAM MENINGKATKAN PENDAPATAN KELUARGA UNTUK MENANGGULANGI KEMISKINAN - Liana, Yuyuk (DINAMIKA DOTCOM, 2016)
The role of women at this time have a big impact for domestic life, because besides in addition to family income but also can improve the welfare of the family. Therefore increased participation of women working to help the economy. It greatly affects the mothers role in the economic life, other than that the woman also has a dual role, namely as the role of mother and wife in the household and the role of women in work that does not interfere with family life. The purpose of this study are: (1) To determine the mothers role in helping the welfare of the family (2) To find out what work is housewives to help welfare families.Â Keywords: the role of women, family welfare, poverty